Interpretation as a factor influencing translation: the case of a biblical metaphor - Kuo, Yun-Hsuan; Chou, Fu-Chu (International Journal of Language, Translation and Intercultural Communication, 2015)
This paper identifies interpretation as a crucial factor influencing translation of biblical metaphors. Data are drawn from five Chinese Bible translations. Qualitative analysis is conducted. The results show that it is highly likely for translators’ interpretation of biblical metaphors to affect the metaphor translation. More researches probing into translation variations of biblical metaphors in Chinese Bible translations are called for.